Population pharmacokinetics/pharmacodynamics and safety of YPEG-rhGH in elderly subjects - He, Yajie; Hu, Jingwen; Zeng, Xin; Yang, Qianfeng; You, Qiuyun; Huang, Jiangeng; Zhang, Yu; Si, Luqin; Zhai, Xuejia (Frontiers in Pharmacology, 2025)
Y-shape branched PEGylated recombinant human growth hormone (YPEG-rhGH) is a suitable drug for the treatment of growth hormone deficiency. The aim of this study was to establish a population pharmacokinetics/pharmacodynamics (PopPK/PD) model of YPEG-rhGH in the elderly. The safety and tolerability of the drug were investigated, and the possibility of flexible dosing regimen was explored. A total of 16 healthy elderly subjects and 36 healthy adults participated in the PopPK analysis. Only elderly subjects were included in the PopPK/PD analysis. After subcutaneous injection of the drug, serum samples were collected to analyze the time course of YPEG-rhGH concentrations and insulin-like growth factor-1 (IGF-1) levels. Additionally, the safety and tolerability of the investigational drug were evaluated. Results show that the pharmacokinetics of serum YPEG-rhGH after subcutaneous injection can be better described by a two-compartment model with first-order absorption and nonlinear elimination. The indirect response model (IDR) demonstrated good predictive capability for the relative baseline ratio of IGF-1 levels in elderly subjects following YPEG-rhGH administration. The magnitude of the increase in the relative baseline ratio of IGF-1 decreased with increasing weight, and increasing age marginally reduced the increase in the baseline ratio of YPEG-rhGH-increased IGF-1 in elderly people, but the effect decreased with increasing dosing intervals. All reported adverse reactions were mild. In the final model, AGE was identified as a significant covariate for Ka, V1/F, and Vmax, while WEIGHT significantly influenced Vmax. The IDR model was consistent with the PK/PD profile of elderly subjects. The safety and tolerability of YPEG-rhGH injections in elderly subjects were favorable.Clinical Trial Registration: identifier CTR20230176.